Strategi pemulihan citra publik pada kementerian pemuda dan olahraga RI: (Studi kasus: Pasca OTT KPK suap dana hibah KONI) - Nisa, Nur Sholekhatun; Samputra, Palupi Lindiasari (Journal of National Paradigm-Based Resilience Strategy, 2024)
The KONI Grant Fund Bribery corruption case at the Ministry of Youth and Sports violated the integrity pact, which decreased public trust. This research aims to analyze the types of image restoration strategies implemented by the Ministry of Youth and Sports and which strategies most influence public trust or can restore the image of the Ministry of Youth and Sports. The research uses a mixed sequential exploratory approach (starting from the qualitative method stage and continuing to the quantitative method). The research results show that the Ministry of Youth and Sports implements six image restoration strategies to increase the level of public trust, namely: reducing offensiveness strategy, mortification strategy, denial strategy, evading of responsibility strategy, and corrective action strategy. A new strategy, the professional imaging strategy, was discovered by the Ministry of Youth and Sports. The results of the causality analysis show that the evading of responsibility and mortification strategies have the most significant influence in increasing public trust. On the other hand, the Ministry of Youth and Sports needs to avoid professional imaging strategies because, statistically, it negatively and significantly decreases public trust. Recommendations from the Ministry of Youth and Sports need to convince the public that the KPK OTT case of KONI Grant bribery does not represent the agency and that the Ministry of Youth and Sports is committed to controlling employee performance by prioritizing integrity.